Information communication technology and climate change adaptation in Somalia: Empirical evidence on awareness, preparedness, agriculture and risk responses - Jarras, Aweis Ahmed Hussein; Hussein, Ali Mohamed (Edelweiss Applied Science and Technology, 2026)
Information and communication technology (ICT) has the theoretical potential to enhance climate resilience; however, its effectiveness in fragile states such as Somalia remains underexplored. This study investigated the relationship between ICT utilization and four climate adaptation dimensions: awareness, disaster preparedness, agricultural decision-making, and risk response. Using a quantitative descriptive design, data were collected from 353 randomly selected ICT users in Somalia through a structured online survey. The predominantly rural, livelihood-based sample showed high mobile phone access (75.6%) but limited smartphone Internet access (40.2%) and significant educational gaps (27.8% with no formal education). Results revealed moderate and uneven ICT contributions: while over half of respondents reported increased climate awareness, trust in digital information was low (mean 2.91/5). Disaster preparedness via ICT was poor, with limited access to early warnings. Agricultural ICT support, particularly for drought-resistant practices, was minimal. However, ICT proved to be more effective for climate risk response, especially through mobile money and voice communication. The study concludes that the current ICT integration in Somalia is insufficient for robust climate adaptation. It recommends locally based, low-tech, accessible solutions prioritizing radio, voice calls, and mobile money, alongside hybrid models that combine digital alerts with traditional sources such as community elders to build trust and resilience in vulnerable, resource-constrained settings.